2020
DOI: 10.1038/s41598-019-57270-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different fertilizer formulas on the growth of loquat rootstocks and stem lignification

Abstract: Grafting is a common method of variety propagation in loquat breeding, the slow growth of rootstocks is a main factor limiting the expansion of this technique. This study aimed to evaluate the effects of seven different fertilizer formulas on the growth of loquat rootstock seedlings, five water-soluble fertilizer formulas, as well as organic fertilizer and controlled-release fertilizer were evaluated. An unfertilized control (CK) was also performed. Growth indicators including plant height, stem thickening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…The lowest number of encompassed internodes was obtained from microelement treated vines. A similar result was found by Xu et al (2020) that the addition of microelements in fertilizer to loquat rootstock seedlings can significantly delay the lignification process of the cambium of grafted vines, which exhibited the greatest improvement in stem thickening. Regular (Caspari et al, 1998) or 90% leaf removal (Chaumont, 1995;Ollat, 1998) reduces photosynthesis.…”
Section: Resultssupporting
confidence: 83%
“…The lowest number of encompassed internodes was obtained from microelement treated vines. A similar result was found by Xu et al (2020) that the addition of microelements in fertilizer to loquat rootstock seedlings can significantly delay the lignification process of the cambium of grafted vines, which exhibited the greatest improvement in stem thickening. Regular (Caspari et al, 1998) or 90% leaf removal (Chaumont, 1995;Ollat, 1998) reduces photosynthesis.…”
Section: Resultssupporting
confidence: 83%
“…Similarly, the growth attributes of rose plants were enhanced when the plants received proper levels of N, P, and K elements [ 67 , 68 ]. Furthermore, the P detected in GE is essential for root development promotion and, consequently, increased the water and nutrient absorption capability [ 69 ]. In agreement with our results, the effective role of several BIOs in improving the vegetative growth of different species has been reported [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FA treatment significantly maintained the RWC and enhanced both tte TCC and TSS relative to untreated plants. A higher RWC in treated leaves may be due to the effect of FA on improving the root system and enhancing water absorption [ 69 ]. In agreement with the current results, the role of FA in increasing the TCC and TSS has been documented in several previous reports [ 48 , 74 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible cause is that the formula or composition of the biofertilizer is not appropriate for the amaranth nutritional requirements. Variations in the type, formula, or concentration of biofertilizers applied to plants could be the factors that contribute to plant development (Xu et al, 2020). On the basis of these results, it may be concluded that stress has no discernible effect on amaranth metaxylem diameter.…”
Section: Resultsmentioning
confidence: 96%